Leaf symptoms of macronutrient deficiencies in two tropical forage legumes - Souto, Sebastião Manhães; Franco, Avílio A. (Pesquisa Agropecuaria Brasileira, 2014)
Two greenhouse experiments were carried out, using glass vessels with aereted "Hoagland" nutrient solution, to study the symptomatology of nutrient deficiencies in Centrosema pubescens Benth., variety Deodoro (jitirana), and Phaseolus atropurpureus D.C., variety Siratro. The lack of N, P, or K stimulated root development in relation to the aerial parts, and was more pronounced in Siratro than Jitirana. In all observations on the 50th day after planting, Siratro showed better development than Jitirana. The symptoms of the nutrient deficiencies presented during the growth of the plants, were described and photographed.